The Sacredization of Women in the Poetry of Nizar Qabbani: A Stylistic Analysis of the Poem “I Testify that There Are No Women but You” - Adam Saputra; Sitti Wahidah Masnani; Haeruddin Haeruddin; Andi Agussalim (Lembaga Bale Literasi, 2025)
Studies on stylistics in modern Arabic poetry that focus on the representation of the sacralization of women through linguistic elements have not been widely done. This research aims to analyze the use of diction and language style and reveal the mechanism of sacralization of women in the poem I Witness No Women Other Than You by Nizar Qabbani. This study uses a qualitative descriptive method with a stylistic approach. The research data was in the form of four poems that were selected using purposive sampling techniques and collected through literature studies, listening techniques, note techniques, and documentation. Data analysis was carried out based on the theory of diction and the style of the Gorys Keraf language supported by Burhan Nurgiyantoro's image theory. The results of the study show that the use of connotative, symbolic, and religious diction combined with the style of hyperbolic language, metaphor, simile, and allusion forms the representation of women as noble and high-value figures. This representation is strengthened by the dominance of visual, movement, and touching imagery that presents an aesthetic experience while deepening poetic meaning. These findings show that the sacredization of women is built through the integration of stylistic elements, so this research is expected to expand the study of the stylistics of modern Arabic literature.